Exploring Job and Family Satisfaction: Scale Validation and Role of Demographic Variables. (December 2019) - Jain, Sarika; Nair, Shreekumar K.
Satisfaction from job is considered as an important variable for study with respect to sales employees. By virtue of their job profile, sales employees are required to respond to multiple demands from multiple stakeholders both at work and family front which eventually lead to negative outcomes such as stress. This in turn results in lesser satisfaction both in work and family domains. Although job satisfaction gets highlighted across researches (especially in western context), family satisfaction still remains a subject of negligence in sales related researches. The present study aims to validate the Job and Family satisfaction in Indian context by exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) using analysis of moment structures (AMOS) software. The results of the data analysis conform the findings of previous literature. Further, this study explored the impact of demographic variables on job and family satisfaction of sales employees. The study contributed to the sales management literature by identifying the key demographic variables that can have an effect on sales employee's job and family satisfaction. Results indicated that sales employee satisfaction from job is associated with both work (tenure in an organization, hierarchy and annual salary) as well as family related domains (marital status). However, family satisfaction is primarily dependent on family related factors. Implications of these findings are discussed.